An exploratory study of a NoSQL database for a clinical data repository - Hak, Francini Abdul (2020)
The need to implement a distributed Clinical Data Repository (CDR) at a healthcare facility, rose in large part due to the high volume of data and the discrepancy of their sources. Over the years, Relational Database Management Systems (RDBMS) began to present difficulties in responding to the needs of various organizations when it comes to manipulating a large amount of data and to its scalability. Therefore, it was necessary to explore other techniques to choose the appropriate technology to build the CDR. In this way, NoSQL emerged as a new type of database that is quite useful to work with multiple and different types of data. In addition, NoSQL introduces a number of user-friendly features such as a distributed, scalable, elastic and also fault tolerant system. In this way, Oracle NoSQL Database was the NoSQL solution chosen to develop this case study, using the key-value storage. This article was motivated to propose a CDR architecture based on Oracle NoSQL Database functionalities. A one-single node database was deployed for better comprehension, in order to enhance their features for future implementation.